InVEST-based assessment of carbon sequestration potentials and environmental dynamics in the coastal area of Lagos - Adedoja, T.B.; Adegboyega, S.A.; Fakpor, A.M. (European Scientific Journal, ESJ, 2025)
Coastal environments comprise multiple arrays of ecosystems, including forests, mangroves, wetlands, and oceans. These ecosystems possess a unique ability to store Carbon for prolonged periods, acting as natural carbon sinks and contributing to reducing atmospheric greenhouse gas concentrations. However, despite their significance, the potential of coastal land covers and their associated land use in mitigating global warming through carbon absorption is often overlooked. This study employed the InVEST (Integrated Valuation of Ecosystem Services and Tradeoffs) model together with Intergovernmental Panel on Climate Change (IPCC) Carbon pool data to assess the carbon stock and dynamics of various land use and land cover types in the coastal environment of Lagos for 20 years. The results revealed a substantial reduction in net stored Carbon from 1.33 x 108 metric tons of Carbon in 2003 to 1.21 x 108 metric tons of Carbon in 2013, which accounts for a 6.66% decline in stored Carbon during that period. Furthermore, the total carbon stock decreased by approximately 3.5 x108 Metric tons, equating to a loss of over 300 million tons between 2013 and 2023. By identifying and measuring the carbon sequestration capacity of these varied coastal land covers, researchers can gain insight into their function in reducing global warming. These natural carbon sinks can be preserved and enhanced by conservation efforts, sustainable management practices, and policy decisions informed by this information, aiding the global fight against climate change.